Implementasi Kebijakan Penataan Pedagang Kaki Lima Di Kota Banjarmasin - Sugiannor Sugiannor (Madika: Jurnal Politik dan Governance, 2022)
Problems of street vendors has been entered into the issue of public order, the Regional Regulation No. Banjarmasin city 26 Year 2012 on the Establishment and Organizational Structure of Civil Service Police Unit Banjarmasin, an organization formed Civil Service Police Unit Banjarmasin which has the main task to maintain and organize public peace and order, enforce local regulation, Regulation and Decision Mayor Mayor as the executor of regional regulation. Mayor of London Based Decision No. 26 Year 2012 on the Establishment and Structuring Control Team Street Vendors of Banjarmasin, explained that the team composition and Arrangement of Control Street Vendors of Banjarmasin, implementing daily field operations conducted by the Civil Service Police Unit Banjarmasin. This study uses qualitative research. Source of data derived from primary data and secondary data, which were collected by interview and documentation. Analysis of the data using a model that consists of a qualitative analysis of data reduction, data display and conclusion. daily field operations conducted by the Civil Service Police Unit Banjarmasin. The results of this study indicate that the regulation number 26 of 2012 is not running as it should. This can be seen from: Lack of communication and coordination between the implementing organization of this local regulations. Less rapid response from the city government and the organization is concerned about street vendors who could potentially become a group that a lot of that in the future will be permasalahan.Kurang specifically the enforcement regulations in the enforcement process so that the vendors long tungginga market that should occupy a place which has provided the city government, being back on the roadside selling belitung. Lack of support of the external environment / community awareness about the importance of the order of their surroundings.